2011
DOI: 10.1097/mcd.0b013e32833ff2e9
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic trisomy 11 in a fetus with bilateral renal agenesis

Abstract: We report a fetus with mosaic trisomy 11 who also had bilateral renal agenesis. We describe the post-mortem examination findings in the fetus and cytogenetic analysis. There are no earlier reports of full trisomy 11, presumably because it is lethal and results in early spontaneous miscarriages. There is only one report published earlier in a fetus with mosaic trisomy 11. There have been a few case reports of trisomy 11 identified in pre-natal samples, where it was associated with normal outcome. Bilateral rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The deletion size of patients helps us to understand phenotype-genotype correlations [Krishnamurti et al, 2001;Fujita et al, 2010]. Mosaic trisomy 11 has been reported earlier by Wilmot et al [1983] and Balasubramanian et al [2010]. Our case Fryns et al, 1986Laleye et al, 2002Giampietro et al, 2006Bernaciak et al, 2008So et al, 2013Tassano et al, 2016 Age showed no mosaic trisomy 11.…”
Section: Discussionsupporting
confidence: 60%
“…The deletion size of patients helps us to understand phenotype-genotype correlations [Krishnamurti et al, 2001;Fujita et al, 2010]. Mosaic trisomy 11 has been reported earlier by Wilmot et al [1983] and Balasubramanian et al [2010]. Our case Fryns et al, 1986Laleye et al, 2002Giampietro et al, 2006Bernaciak et al, 2008So et al, 2013Tassano et al, 2016 Age showed no mosaic trisomy 11.…”
Section: Discussionsupporting
confidence: 60%
“…Trisomy 11 was detected in one fetus (POC39). Full trisomy 11 has not been reported in live births and presumably leads to early pregnancy loss (Balasubramanian et al, 2011). Few cases with partial trisomy 14q were reported with carrying pericentric inversion in one of the parents and proband with recombinant chromosome 14 (Kurtulgan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Trisomy 11 was detected in one fetus (POC39). Full trisomy 11 has not been reported in live births and presumably leads to early pregnancy loss ( Balasubramanian et al, 2011 ). Few cases with partial trisomy 14q were reported with carrying pericentric inversion in one of the parents and proband with recombinant chromosome 14 ( Kurtulgan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%